Application and practice of trimodal prehabilitation model in preoperative management of patients with lung cancer undergoing video-assisted thoracoscopic surgery - Yao, Liping; Chen, Hui; Xue, Bei (Frontiers in Surgery, 2023)
Lung cancer is one of the malignant tumors with high mortality worldwide. To date, the most effective treatment of non—small cell lung cancer (NSCLC) is still surgical resection. Video-assisted thoracoscopic surgery has become the main surgical approach. Tumor patients are the high-risk perioperative population. At present, how to optimize perioperative management measures to improve the patient's body function and promote the rehabilitation after video-assisted thoracoscopic surgery is a hot research topic for medical staff. In this study, 148 patients with lung cancer were selected as the research object, to analyze and discuss the application value of trimodal prehabilitation model in preoperative management of patients with lung cancer undergoing video-assisted thoracoscopic surgery.